Gestão digital do aprendizado pessoal - Silva, Daniel Filisetti Marcos da (2016)
When it comes to digital and internet technology, it comes to mind the access to an infinite world of information. On the other hand, in life, we learn an enormous quantity of knowledge that is stored in our memory and is spread in files, folders and texts, either digital or physical. This thesis proposes to look at this inner immensity of knowledge and to investigate how digital technology can be used to organize, register and access it in an efficient and lasting way. Parallel to learning, the human brain works in constant changing, and what we learn we store in the long-term memory. The digital management of personal learning will play a role of partnership in relation to our memory. The reason is that it will bring concrete elements that will direct resonance what we learn and memorize, along with the digital records and the paths we have traveled to get to the acquisition of knowledge. Through literature review, this text makes the connection, analysis and convergence in three major areas of study. These are: human memory, constructivist learning theory and digital technologies. Related to human memory, its divisions and classifications are analyzed, especially long-term memory, working memory and their central executive subdivisions, phonological loop, visuospatial sketch and episodic retainer. Another aspect addressed is the importance of writing for both memory and for development of ideas and simple or complex reasoning. Authors such as Lent, Baddeley, Pozo, among others, will be assayed. In constructivist learning, the importance of prior learning and anchorage conditions of a new object of knowledge is discussed. Piaget and Ausubel s concepts of assimilation and accommodation, progressive differentiation and integrative reconciliation are analyzed. Another important concept is the delayed and early revisiting in the learning process. In digital technology, the thesis contextualizes the importance of cloud storage, mobile and compact devices, the hologram technology, wearable devices and knowledge recording software. Existing technologies (2015) and those foreseen in a horizon of two decades are discussed. Finally, the study proposes an orchestration of digital technologies, taking into account the analyzes done, and it comes to the conclusion that the technology will bring a new paradigm of how we will make the management of personal learning through digital devices and technologies